1996
DOI: 10.1002/abio.370160219
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the antibiotic activity of tea fungus/kombucha beverage

Abstract: Tea fungus/kombucha, an acetic acid flavoured fermented tea beverage, is widely consumed in various parts of the world and has more recently become a fad in the United States. This is due in part to the fact that it can be produced in the home, and it is reported to be medicinal, effective against arthritis, psoriasis, chronic fatigue, constipation, indigestion and metabolic diseases. Among 264 references from 1852 to 1961, there are reports of.antibiotic activity against Agrobacterium tumefaciens and medicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 12 publications
2
35
0
3
Order By: Relevance
“…The results of antibacterial activity of kombucha beverages with diff erent TA and control samples confi rm previous suppositions that acetic acid is the dominant active component of kombucha (2,56,57). More acidic beverage had higher inhibition zones (Table 4), which proves that the intensity of the antimicrobial activity of kombucha is directly related to the concentration of acetic acid.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The results of antibacterial activity of kombucha beverages with diff erent TA and control samples confi rm previous suppositions that acetic acid is the dominant active component of kombucha (2,56,57). More acidic beverage had higher inhibition zones (Table 4), which proves that the intensity of the antimicrobial activity of kombucha is directly related to the concentration of acetic acid.…”
Section: Discussionsupporting
confidence: 72%
“…However, the levels of tea above 4.4 g/L had an off ensive bi er taste and were undrinkable (63). The absence of or an insignifi cant antimicrobial activity of black and green teas at drinkable levels could be explained by the low concentrations of tea and its active components (polyphenols/tannins) (56,59). Also, unfermented winter savory (Satureja montana L.) tea at 5 g/L did not show antimicrobial activity against the tested microorganisms (57).…”
Section: Discussionmentioning
confidence: 99%
“…The observed antimicrobial activity was due to the organic acids, primarily acetic acid, and was eliminated when samples were neutralized. Many studies on kombucha have proven that its antimicrobial activity against pathogenic microorganisms is largely attributable to acetic acid (Steinkraus et al 1996), which is a known antimicrobial agent (Sreeramulu et al 2000). Adams (1985) demonstrated that pathogenic and spore-forming bacteria were inhibited at as little as 1 g/l of acetic acid.…”
Section: Changes In Chemical and Microbiological Parameters During Fementioning
confidence: 99%
“…Numerous popular media features in the U.S.A. have highlighted the beverage and its uses, including the New York Times and Miami Herald, suggesting that Kombucha consumption can reduce blood pressure, relieve arthritis, increase the immune response, and cure cancer (2,3). Kombucha lends itself to expansive consumption as a healthful beverage as it is easily and safely produced at home (4). Production of the tea is achieved by infusing tea leaves in freshly boiled water and sweetening it with about 100 g/L sucrose or honey.…”
Section: Introductionmentioning
confidence: 99%